Sirvent Gutiérrez, Consuelo, y López Durán, Rosalío, Alfred Dreyfus. Injusticia y razón de Estado, México, Porrúa, 2019, 82 pp. - Jiménez Moreno, Manuel de J. (Revista de la Facultad de Derecho de México, 2019)
.